Coordination and pricing decisions in a closed-loop supply chain. (2018) - Faramarzi, Hamid; Castillo, Ignacio
This paper investigates coordination and pricing decisions in a closed-loop supply chain (CLSC) with a manufacturer, a remanufacturer, and a retailer. We also consider a supplier who provides both the manufacturer and remanufacturer with new parts. We follow the practice by assuming vertically differentiated new and remanufactured products. We show how the optimal prices and quantities for new and remanufactured products at the retailer level, and the total CLSC profits and the supplier's profits compare with each other across different CLSC coordination structures. We also investigate the sensitivity of our results to the quality of returns and consumers' perceptions. We find that both the CLSC and the supplier enjoy the highest profits from the coordination between the retailer and the manufacturer. Furthermore, we show that the coordination between the retailer and the remanufacturer results in the lowest profits for the CLSC members, but not necessarily the lowest for the supplier.